Who pays the price? -Socio-ecological controversies regarding the energy transition in South America (Sustainability in Debate, 2022)
Transformations linked to more sustainable energy and economic systems may have societal and ecological costs, which some people and territories must assume. Controversies might emerge associated with developing new productive chains, e.g., transition mineral activity. This study examines the relations among energy transition, society, and the environment, focusing on copper as a high-tech mineral and considering Bolivia, Chile, and Peru, three countries with mining-dependent economies.This work tries to see if countries are becoming more renewable, efficient, and modern and if this correlates with copper activity and societal factors. As a result, Bolivia has pending tasks on both the energy demand and production sides. Despite presenting good performance on renewables and efficiency, Chile and Peru have pending tasks associated with the ecological distribution regarding mining and energy sectors. Mining-based economies might expose the fragility of green transitions in meeting sustainable goals considering equality, justice, and ecosystem care.